Структурно-функциональные изменения в организме крыс при развитии экспериментальной гиперчувствительности организма и возможность коррекции их введением солкосерила = Structural and functional changes in the organism of rats with hypersensitivity development of experimental organisms and the possibility of correcting their introduction solkoseril - Pochtar, V. N.; Nasibullin, B. A. (Journal of Education, Health and Sport, 2016)
Pochtar V. N., Nаsibullin B. А. Структурно-функциональные изменения в организме крыс при развитии экспериментальной гиперчувствительности организма и возможность коррекции их введением солкосерила = Structural and functional changes in the organism of rats with hypersensitivity development of experimental organisms and the possibility of correcting their introduction solkoseril. Journal of Education, Health and Sport. 2016;6(9):276-284. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61761 http://ojs.ukw.edu.pl/index.php/johs/article/view/3843 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016. СТРУКТУРНО-ФУНКЦИОНАЛЬНЫЕ ИЗМЕНЕНИЯ В ОРГАНИЗМЕ КРЫС ПРИ РАЗВИТИИ ЭКСПЕРИМЕНТАЛЬНОЙ ГИПЕРЧУВСТВИТЕЛЬНОСТИ ОРГАНИЗМА И ВОЗМОЖНОСТЬ КОРРЕКЦИИ ИХ ВВЕДЕНИЕМ СОЛКОСЕРИЛА 1В. Н. Почтарь, 2Б. А. Насибуллин 1Украинский НИИ стоматологии НАМН Украины, Одесса 2ГУ "Украинский НИИ медицинской реабилитации и курортологии", Одесса Резюме Авторы, по результатам исследований 65 белых крыс линии Вистар аутбредного разведения, у которых моделировали гиперчувствительность иммунной системы замедленного типа и травму слизистой щеки, выявили системное нарушение дизрегуляционного характера в виде ослабления дифференциации эпителиоцитов, снижении активности NO˗S и накоплении липидов в кишечнике и аорте. Эти изменения формировались на фоне дистрофических изменений лимфоидных фолликул стенки кишечника. Курс солкосерила восстанавливал структуру фолликул и нормализовал остальные исследуемые показатели. Авторы полагают, что изменение лимфоидных фолликул способствует развитию дизрегуляционных и аутоиммунных процес сов в организме, что делает возможным формирование МЭЭ. Солкосерил, в силу своих свойств (стимулятор репарации), оказывал положительное влияние не только на эпителий, но и на структурно-функциональную организацию лимфоузлов, что способствовало снижению аутоиммунных реакций. Ключевые слова: гиперчувствительность иммунной системы; солкосерил; фолликулы, NO˗синтаза; экссудативная эритема. STRUCTURAL AND FUNCTIONAL CHANGES IN THE ORGANISM OF RATS WITH HYPERSENSITIVITY development of experimental organisms and the possibility of correcting their introduction solkoseril 1V. N. Pochtar, 2B. А. Nаsibullin 1Ukrainian Research Institute of Dental Academy of Medical Sciences Ukraine 2The Ukrainian scientific and research institute of medical rehabilitation and balneology of the Ministry of health of Ukraine, Odessa, Ukraine Abstract The authors, based on the results of research of 65 white outbred Wistar rats breeding in which simulated hypersensitivity of the immune system and delayed-type injury buccal mucosa revealed a systemic disorder dizregulyatsionnogo nature in the form of weakening the differentiation of epithelial cells, reducing NO˗S activity and the accumulation of lipids in the intestine and aorta. These changes are formed on the background of degenerative changes in the lymphoid follicles of the intestinal wall. Course solcoseryl restoring the follicle structure and normalized the remaining studied parameters. The authors suggest that a change in the lymphoid follicles contributes to the development of autoimmune processes dizregulyatsionnyh and owls in the body, which makes possible the formation of the magnetoelectric effect. Solkoseril, by virtue of its properties (repair stimulant), had a positive impact not only on the epithelium, but also on the structural and functional organization of the lymph nodes, which contributed to the reduction of autoimmune reactions. Keywords: hypersensitivity of the immune system; solkoseril; follicles NO˗sintaza; erythema.